ANALYSIS OF AN ADULT DUCHENNE MUSCULAR DYSTROPHY POPULATION: TEN YEARS ON. Issue 11 (14th October 2015) - Wu, Kit; Rigaudy, Axelle; Christodoulou, Loucas; Okello, Aren; Ballard, Emily; Hart, Nicholas; Howard, Robin
Abstract : Background: Duchenne muscular dystrophy (DMD) is a progressive, multi-systemic condition, management of which has benefitted from improvements in research and healthcare. Aim: 1. To review the multidisciplinary management of a late adolescent and adult DMD population attending the Lane Fox Respiratory Unit. 2. To compare the findings to those of an audit conducted 10 years previously (Parker et al, QJM. 2005.), so to identify areas of improvement and issues that require further input. Method: We studied 30 patients with DMD referred to an adult neuromusclular clinic over a ten-year period. Clinical details were obtained from case notes or direct observations. Results: The age for our cohort ranged from 19 to 49 years, all of whom became symptomatic before ten years old. Nine patients died during the study period. 25 patients were wheelchair bound in their mid-teens. Over the last ten years, areas of improvement include provision of non-invasive ventilation, provision of aids, and access to education (9/30 of our cohort attended university or college, and three patients are in active employment). Areas of care that need further input are management of mood, bowel hygiene, fatigue and pain. Discussion: Despite improvements in several areas, there is still a need for a consistent and multi-faceted approach to management of DMD.